Pengetahuan Dan Sikap Wisatawan Asing Di Bali Terhadap Dental Tourism - Samuel Pramadisa; Steffano Aditya Handoko; Ni Made Sri Nopiyani (School of Dentistry Faculty of Medicine Udayana University, 2022)
Introduction: The development of dental tourism has grown globally. Dental tourism is a search for dental and oral health care in other countries. Bali has the potential to develop the dental tourism industry. The purpose of this study was to determine the knowledge and attitudes of foreign tourists in Bali towards dental tourism. Method: A cross-sectional descriptive study has been carried out with a sample of 98 foreign tourists at International Departure Terminal I Gusti Ngurah Rai Airport. Respondents were given questionnaires with closed questions to evaluate their knowledge and attitudes towards dental tourism. The data were obtained then analyzed descriptively and displayed in the form of a frequency distribution table. Results: As many as 46.9% of respondents had heard of dental tourism, while only 15% knew of dental tourism services in Bali. The dominant source of information is by word of mouth. Most respondents only knew two factors driving dental tourism. Respondents knew all the treatment options available in the questionnaire. Respondent’s attitude towards dental tourism shows uncertainty. As many as 68.4% of respondents said they were not interested in dental tourism, of which 76.2% said they were satisfied with care in their home countries. Conclusion: In general, foreign tourist’s knowledge of dental tourism was low. The general attitude of tourists to dental tourism shows uncertainty and interest in low dental tourism. It is recommended to increase promotion effectively and creatively by utilizing internet to support the potential of dental tourism. Latar Belakang: Perkembangan dental tourism telah berkembang secara global. Dental tourism adalah perilaku pencarian perawatan kesehatan gigi dan mulut di negara lain. Bali sangat berpotensi untuk mengembangkan industri dental tourism. Tujuan dari penelitian ini adalah untuk mengetahui pengetahuan dan sikap wisatawan asing di Bali terhadap dental tourism. Metode: Telah dilakukan penelitian deskriptif cross-sectional dengan sampel 98 wisatawan asing di Terminal Keberangkatan Internasional Bandar Udara I Gusti Ngurah Rai. Responden diberikan kuesioner dengan pertanyaan tertutup untuk mengevaluasi pengetahuan dan sikap mereka terhadap dental tourism. Data yang diperoleh kemudian dianalisis secara deskriptif dan ditampilkan dalam bentuk tabel distribusi frekuensi. Hasil: Sebanyak 46,9% responden pernah mendengar mengenai dental tourism, sementara hanya 15% yang mengetahui layanan dental tourism di Bali. Sumber informasi dominan dari mulut ke mulut. Sebagian besar responden hanya mengetahui dua faktor pendorong dental tourism. Responden telah mengetahui seluruh pilihan perawatan yang umum dilakukan pada dental tourism. Sikap responden terhadap dental tourism menunjukan ketidakyakinan. Sebanyak 68,4% responden mengaku tidak tertarik dengan dental tourism, dimana 76,2% diantaranya mengaku puas dengan perawatan di negara asal mereka. Kesimpulan: Secara umum, pengetahuan wisatawan asing terhadap dental tourism rendah. Sikap secara umum wisatawan terhadap dental tourism menunjukan ketidakyakinan dan ketertarikan terhadap dental tourism rendah. Disarankan untuk meningkatkan promosi secara efektif dan kreatif dengan memanfaatkan media internet untuk mendukung potensi dental tourism.